2016
DOI: 10.1371/journal.pone.0159407
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Multipurpose Timber Yielding Tree Neolamarckia cadamba during Xylogenesis Using RNA-Seq

Abstract: Neolamarckia cadamba is a fast-growing tropical hardwood tree that is used extensively for plywood and pulp production, light furniture fabrication, building materials, and as a raw material for the preparation of certain indigenous medicines. Lack of genomic resources hampers progress in the molecular breeding and genetic improvement of this multipurpose tree species. In this study, transcriptome profiling of differentiating stems was performed to understand N. cadamba xylogenesis. The N. cadamba transcriptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 74 publications
0
20
0
2
Order By: Relevance
“…Owing to these utilizable economic value, it is affectionately known as the "miracle tree. " In the past few years, N. cadamba has increasingly attracted the attention of research groups especially in phytochemical and biomolecular field (Chaubey et al 2015;Li et al 2017;Ouyang et al 2016;Zhao et al 2014). Phytochemical studies have revealed various biologically active compounds from root, bark, leaves and fruits of N. cadamba, including alkaloids, flavonoids, terpenoids and saponins, etc (Acharyya et al 2013;Chandel et al 2012;Pandey and Negi 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to these utilizable economic value, it is affectionately known as the "miracle tree. " In the past few years, N. cadamba has increasingly attracted the attention of research groups especially in phytochemical and biomolecular field (Chaubey et al 2015;Li et al 2017;Ouyang et al 2016;Zhao et al 2014). Phytochemical studies have revealed various biologically active compounds from root, bark, leaves and fruits of N. cadamba, including alkaloids, flavonoids, terpenoids and saponins, etc (Acharyya et al 2013;Chandel et al 2012;Pandey and Negi 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, triterpenoid saponins have been identified as the important active components in medicinal plants (Augustin et al 2011). Recent study found that higher abundant transcripts related to triterpenoid saponin and phytosterol biosynthesis were existed in N. cadamba (Ouyang et al 2016). Medicinal properties of N. cadamaba might be due to the presence of these bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Neolamarckia cadamba is a very important tropical hardwood tree. RNA-seq analyses of the N. cadamba transcriptome have identified 55,432 UniGenes and 47.8% of the UniGenes have been annotated against publically available protein databases and 5589 UniGenes have been mapped onto 116 pathways (Ouyang et al 2016). RNA-seq technology has been used to investigate xylogenesis in N. cadamba and the results derived from RNA-seq analyses demonstrated that genes related to heteroxylan synthesis had higher expression in the basal part of the stem compared to the apical part (Zhao et al 2014).…”
Section: Neolamarckia Cadambamentioning
confidence: 99%
“…Essa abrangência nos resultados da categorização funcional inicial também foi constatada em outros trabalhos que utilizaram essa metodologia (Domingos et al, 2016;Ouyang et al, 2016;Xu et al, 2016). xilanas e dos fenilpropanoides, assim como, a sinalização mediada pelo etileno e a atividade catalítica das peroxidases, tudo isso trabalhando em conjunto para possibilitar a completa formação e funcionalidade dos elementos traqueais.…”
Section: Obtenção In Vitro E Caracterização Morfológica Dos Elementosunclassified
“…O fator de transcrição MYB63 foi relatado como especificamente expresso em fibras e vasos submetidos ao espessamento da parede secundária atuando como um importante regulador da biossíntese de lignina em várias espécies, inclusive em eucalipto (Hefer et al, 2015;Ouyang et al, 2016;Zhang et al, 2016;Zhou et al, 2009), além de acreditar-se que os genes LAC4 e LAC17 são regulados por esse fator de transcrição (Zhou et al, 2009). Taylor-Teeples et al (2015) ainda demostrou que o MYB63 regula a expressão do gene CESA8 e de quatro genes da rota biossintética da lignina (C4H, 4CL1, HCT e CCoAOMT1), comprovando a relevância da sua participação na formação dos elementos traqueais.…”
Section: Regulação Transcricional Da Biossíntese Da Parede Celular Seunclassified